Предмет: Алгебра,
автор: NICCCK42141421
докажите, что уравнение (2x+1)3 - (x-4)2 = (x+5)6 не имеет корня
Ответы
Автор ответа:
0
(2x+1)/3 - (x-4)/2 = (x+5)/6 |*6
2(2x+1)-3(x-4)=x+5
4x+2-3x+12=x+5
x+14=x+5
x-x=5-14
0=-9 - равенство ложное
Следовательно, корней нет
2(2x+1)-3(x-4)=x+5
4x+2-3x+12=x+5
x+14=x+5
x-x=5-14
0=-9 - равенство ложное
Следовательно, корней нет
Похожие вопросы
Предмет: Другие предметы,
автор: arinazalasina
Предмет: Русский язык,
автор: zhansaya123429
Предмет: Геометрия,
автор: Tizoner
Предмет: Математика,
автор: Kykolka1996